Pixel to Picture and Picture to Person - Sharma, Rabin K. (Journal on Geoinformatics, Nepal, 2018)
Remotely sensed data are related with the words pixel and resolution as the picture is formed from the pixel having the size defined by the value of resolution of the data. There are unlimited sectors where remote sensing technology can be applied to uplift the social status of the people. In order to make best use of this system, Regional Workshop on Himalayan GEOSS was organized in Nepal. The workshop developed a concept “pixel to picture and picture to person” based on the technology related to Earth observation. The concept to be used for the several sectors identified by the workshop which are also related with the Social benefit areas of the Global Earth Observation System of Systems (GEOSS) of Group on Earth Observation (GEO). Therefore, this paper tries to summarize the result of the workshop in this particular theme.